2001
DOI: 10.1016/s0167-8809(00)00297-8
|View full text |Cite
|
Sign up to set email alerts
|

A model for fossil energy use in Danish agriculture used to compare organic and conventional farming

Abstract: Knowledge about fossil energy use in agricultural systems is needed, because it can improve the understanding of how to reduce the unsustainable use of limited energy resources and the following greenhouse gas emissions. This study describes and validates a model to assess fossil energy use in Danish agriculture; gives an example of how the model can be used to compare organic and conventional farming; and discusses the implications and potentials of using the model to simulate energy use in scenarios of agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
207
1
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 370 publications
(224 citation statements)
references
References 21 publications
4
207
1
12
Order By: Relevance
“…In most LCA/CF studies, farm energy use is modeled and a critical review of the accuracy of input data is important. In a Danish study, which measured actual diesel fuel use on commercial farms to validate a farm energy model, Dalgaard et al (2001) found a systematic underestimate of energy used for transportation and handling of roughage crops and manure in present models of livestock farms.…”
Section: Deforestationmentioning
confidence: 90%
“…In most LCA/CF studies, farm energy use is modeled and a critical review of the accuracy of input data is important. In a Danish study, which measured actual diesel fuel use on commercial farms to validate a farm energy model, Dalgaard et al (2001) found a systematic underestimate of energy used for transportation and handling of roughage crops and manure in present models of livestock farms.…”
Section: Deforestationmentioning
confidence: 90%
“…In a recent review of almost 300 studies comparing yields of organic/agroecological and conventional agriculture throughout the world, it was found that, on average, organic and agroecological systems produce as much, if not more, than conventional systems (72), corroborating many other studies (73)(74)(75)(76)(77). Furthermore, it has now been well-established that energy efficiency in traditional and many organic systems is higher than in high-industrial/conventional agriculture (78)(79)(80)(81).…”
Section: Convergence Of Food Production With Nature Conservationmentioning
confidence: 99%
“…However, intensive use of energy causes problems threatening public health and environment. Efficient use of energy in agriculture will minimize environmental problems, prevent destruction of natural resources, and promote sustainable agriculture as an economical production system (Dalgaard et al 2001).…”
mentioning
confidence: 99%